Exploit and Replace: An Asymmetrical Two-Stream Architecture for Versatile Light Field Saliency Detection - Piao, Yongri; Rong, Zhengkun; Zhang, Miao; Lu, Huchuan (Proceedings of the AAAI Conference on Artificial Intelligence, 2020)
Light field saliency detection is becoming of increasing interest in recent years due to the significant improvements in challenging scenes by using abundant light field cues. However, high dimension of light field data poses computation-intensive and memory-intensive challenges, and light field data access is far less ubiquitous as RGB data. These may severely impede practical applications of light field saliency detection. In this paper, we introduce an asymmetrical two-stream architecture inspired by knowledge distillation to confront these challenges. First, we design a teacher network to learn to exploit focal slices for higher requirements on desktop computers and meanwhile transfer comprehensive focusness knowledge to the student network. Our teacher network is achieved relying on two tailor-made modules, namely multi-focusness recruiting module (MFRM) and multi-focusness screening module (MFSM), respectively. Second, we propose two distillation schemes to train a student network towards memory and computation efficiency while ensuring the performance. The proposed distillation schemes ensure better absorption of focusness knowledge and enable the student to replace the focal slices with a single RGB image in an user-friendly way. We conduct the experiments on three benchmark datasets and demonstrate that our teacher network achieves state-of-the-arts performance and student network (ResNet18) achieves Top-1 accuracies on HFUT-LFSD dataset and Top-4 on DUT-LFSD, which tremendously minimizes the model size by 56% and boosts the Frame Per Second (FPS) by 159%, compared with the best performing method.